Fever treatment in the absence of malaria transmission in an urban informal settlement in Nairobi, Kenya. - Ye, Y; Madise, N; Ndugwa, R; Ochola, S; Snow, R (BioMed Central, 2009)
BACKGROUND: In sub-Saharan Africa, knowledge of malaria transmission across rapidly proliferating urban centres and recommendations for its prevention or management remain poorly defined. This paper presents the results of an investigation into infection prevalence and treatment of recent febrile events among a slum population in Nairobi, Kenya. METHODS: In July 2008, a community-based malaria parasite prevalence survey was conducted in Korogocho slum, which forms part of the Nairobi Urban Health and Demographic Surveillance system. Interviewers visited 1,069 participants at home and collected data on reported fevers experienced over the preceding 14 days and details on the treatment of these episodes. Each participant was tested for malaria parasite presence with Rapid Diagnostic Test (RDT) and microscopy. Descriptive analyses were performed to assess the period prevalence of reported fever episodes and treatment behaviour. RESULTS: Of the 1,069 participants visited, 983 (92%) consented to be tested. Three were positive for Plasmodium falciparum using RDT; however, all were confirmed negative on microscopy. Microscopic examination of all 953 readable slides showed zero prevalence. Overall, from the 1,004 participants who have data on fever, 170 fever episodes were reported giving a relatively high period prevalence (16.9%, 95% CI:13.9%-20.5%) and higher among children below five years (20.1%, 95%CI:13.8%-27.8%). Of the fever episodes with treatment information 54.3% (95%CI:46.3%-62.2%) were treated as malaria using mainly sulphadoxine-pyrimethamine or amodiaquine, including those managed at a formal health facility. Only four episodes were managed using the nationally recommended first-line treatment, artemether-lumefantrine. CONCLUSION: The study could not demonstrate any evidence of malaria in Korogocho, a slum in the centre of Nairobi. Fever was a common complaint and often treated as malaria with anti-malarial drugs. Strategies, including testing for malaria parasites to reduce the inappropriate exposure of poor communities to expensive anti-malarial drugs provided by clinical services and drug vendors, should be a priority for district planners.